(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-12-19 ‘Time to do smth’ as a form of time is considered as the event time. The event of this period of time demonstrates incompletness of a man: it is the most striking example of the adogmatism of Chekhov’s artistic thinking. ‘Time to do smth’, first of all, the time of being, where a person is thrown by the fact of birth, coming into the world, but ‘the time is ripe’ is also the time of an existential choice, living one’s life here and now. The action is discredited in Chekhov’s drama the action is discredited. The actions of the heroes of ‘now’ depend on ‘the time is ripe’ that was hidden from them. In this form of hidden historical, social, and psychological factors are revealed to the characters. It is also time for the hero’s personal existence to become free from illusions. This is exactly the side of ‘Time to do smth’ that is emphasized by A. Chekhov. One of the forms of liberation from the illusions is “patience”, stoicism. Key words: Chekhov, drama, event, existence, forms of time